2023
DOI: 10.3390/agronomy13051210
|View full text |Cite
|
Sign up to set email alerts
|

Application of 6-Pentyl-α-Pyrone in the Nutrient Solution Used in Tomato Soilless Cultivation to Inhibit Fusarium oxysporum HF-26 Growth and Development

Abstract: Soilless cultivation has increased in China. Like vegetables or ornamental plants, tomatoes can be cultivated in soilless culture systems. Fusarium wilt (FW) is an economic tomato disease. The nature and amount of volatile organic compounds in Trichoderma asperellum PT-15 were investigated, and 6-pentyl-α-pyrone (6-PP) was detected. Furthermore, the effect of 6-PP on Fusarium oxysporum HF-26 was evaluated. Results revealed that 25 mg/L 6-PP was the optimal concentration inhibiting F. oxysporum HF-26 and that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…This unsaturated lactone has a coconut-like smell and has applications as a food aroma enhancer. The pronounced antagonistic effects of 6PP against various fungi have been extensively studied [30,31]. Its ability to inhibit the growth of plant pathogenic fungi, protect from postharvest pathogens, and suppress mycotoxins has gained significant attention.…”
Section: Discussionmentioning
confidence: 99%
“…This unsaturated lactone has a coconut-like smell and has applications as a food aroma enhancer. The pronounced antagonistic effects of 6PP against various fungi have been extensively studied [30,31]. Its ability to inhibit the growth of plant pathogenic fungi, protect from postharvest pathogens, and suppress mycotoxins has gained significant attention.…”
Section: Discussionmentioning
confidence: 99%
“…The 6-PP has a significant inhibitory effect on turf dollar spot and recorded good control efficacy recorded both in in-vitro and in-vivo studies [70]. The 6-PP reported from T. asperellum PT-15 showed the antifungal effects by applying a nutrient solution containing 25 mg/L 6-PP significantly suppressed the fusarium wilt with 70.71% efficacy and a 27.23% disease index [71].…”
Section: Discussionmentioning
confidence: 99%
“…Soil-less cultivation methods like hydroponics and substrate culture offer an alternative to traditional soil-based plant growth. When 6-PP was incorporated into soil-less solutions, it effectively suppressed Fusarium wilt of tomato caused by Fusarium spp., significantly reducing the disease index compared to the untreated control (Hao et al, 2023). Additionally, 6-PP induced the downregulation of toxin biosynthesis and transport encoding genes (such as FUB1, FUB4, and FUB10), as well as growth-related genes (VelA, VelB, and LaeA), resulting in decreased growth and hyphae formation of F. oxysporum (Hao et al, 2023) (Figure 3B).…”
Section: Alteration Of Gene Expressionmentioning
confidence: 96%
“…4 Effect of 6-PP on plant pathogens 6-PP has potent antifungal activities, disrupting fungal growth and pathogen development (Degani et al, 2021;Elhamouly et al, 2022;Hao et al, 2023). In a dose-response experiment, Hao et al (2023) showed that 25 mg/L of 6-PP in Hoagland nutrient solution inhibited F. oxysporum growth by up to 70%.…”
Section: Reactive Oxygen Species and 6-ppmentioning
confidence: 99%